Impact of Digital Health Interventions on Managing Chronic Diseases Among Middle Eastern Populations - Sarah Al-Harbi; Ahmed Al-Nuaimi (Generasi Sains Indonesia, 2025)
This study examines the adoption and effectiveness of digital health interventions in managing chronic diseases among Middle Eastern populations, particularly in Kuwait, Saudi Arabia, and the United Arab Emirates. Using a quantitative cross-sectional design, data were collected from 500 participants diagnosed with diabetes, cardiovascular disease, and hypertension through structured survey questionnaires. The findings indicate that 70% of respondents actively used digital health technologies, with mobile health applications representing the most frequently utilized intervention. The study further reveals that digital health usage significantly improved medication adherence, symptom monitoring, and overall disease management outcomes. Education level, income, and frequency of technology use positively influenced perceived effectiveness, while age demonstrated a negative association with digital health utilization. The novelty of this research lies in its comparative regional analysis integrating demographic, socioeconomic, and behavioral dimensions of digital healthcare adoption. The study highlights the importance of strengthening digital literacy, expanding healthcare infrastructure, and developing inclusive digital health policies to support sustainable chronic disease management across Middle Eastern healthcare systems.